Improving Reporting of Clinical Studies Using the POSEIDON Criteria: POSORT Guidelines - Esteves, Sandro C.; Conforti, Alessandro; Sunkara, Sesh K.; Carbone, Luigi; Picarelli, Silvia; Vaiarelli, Alberto; Cimadomo, Danilo; Rienzi, Laura; Ubaldi, Filippo Maria; Zullo, Fulvio; Andersen, Claus Yding; Orvieto, Raoul; et al. (Frontiers in Endocrinology, 2021)
The POSEIDON (Patient-Oriented Strategies Encompassing IndividualizeD Oocyte Number) criteria were developed to help clinicians identify and classify low-prognosis patients undergoing assisted reproductive technology (ART) and provide guidance for possible therapeutic strategies to overcome infertility. Since its introduction, the number of published studies using the POSEIDON criteria has increased steadily. However, a critical analysis of existing evidence indicates inconsistent and incomplete reporting of critical outcomes. Therefore, we developed guidelines to help researchers improve the quality of reporting in studies applying the POSEIDON criteria. We also discuss the advantages of using the POSEIDON criteria in ART clinical studies and elaborate on possible study designs and critical endpoints. Our ultimate goal is to advance the knowledge concerning the clinical use of the POSEIDON criteria to patients, clinicians, and the infertility community.